2005
DOI: 10.1002/ejoc.200500413
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Oligonucleotide Incorporation of Nucleoside Analogues Containing Pendant Imidazolyl or Amino Functionalities – The Search for Sequence‐Specific Artificial Ribonucleases

Abstract: Keywords: Oligonucleotides / Nucleosides / Modified nucleosides / Artificial ribonucleaseOligonucleotide derivatives containing imidazolyl and amino functionalities have been proposed as artificial ribonucleases that might mimic the activities of RNase A but with greater sequence specificity. Such oligonucleotide reagents would have important applications as enhanced antisense reagents that obviate the need to recruit a cellular nuclease or nuclease complex. We present the syntheses of six nucleoside phosphora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 58 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…10,12 C4 triazoles 17–21 and tetrazoles 2226 are common, stable reactive pyrimidine derivatives that have seen wide applications for nucleoside and nucleic acid modifications. A range of aryl sulfonates (Ar = p -toluenesulfonyl, 2-mesitylenesulfonyl, 2,4,6-triisopropylbenzenesulfonyl), 2732 have also been explored as reactive reagents, not only for direct substitution reactions, but also for cross-coupling chemistry. 16,33 Among these, the 2,4,6-triisopropylbenzenesulfonyl derivatives have been shown to be reasonably stable but the 2-mesitylenesulfonyl analogues are not quite as stable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,12 C4 triazoles 17–21 and tetrazoles 2226 are common, stable reactive pyrimidine derivatives that have seen wide applications for nucleoside and nucleic acid modifications. A range of aryl sulfonates (Ar = p -toluenesulfonyl, 2-mesitylenesulfonyl, 2,4,6-triisopropylbenzenesulfonyl), 2732 have also been explored as reactive reagents, not only for direct substitution reactions, but also for cross-coupling chemistry. 16,33 Among these, the 2,4,6-triisopropylbenzenesulfonyl derivatives have been shown to be reasonably stable but the 2-mesitylenesulfonyl analogues are not quite as stable.…”
Section: Introductionmentioning
confidence: 99%
“…27 By contrast, a p -toluenesulfonyl pyrimidine nucleoside was used directly after preparation. 32 Pyrimidine C4 tosylates have also been converted to N -methylpiperidinyl and N -methylpyrrolidinyl salts, as reactive nucleoside analogues. 34 …”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of the imidazole-modified nucleoside from thymidine is achieved in three steps as described by Holmes and Gait ( 27 ). In a first step, a palladium-catalyzed one-pot carboxamidation reaction is used to attach histamine (Sigma-Aldrich) to 5-iodo-2‘-deoxyuridine (Sigma-Aldrich) via an amide bond.…”
Section: Methodsmentioning
confidence: 99%
“…However, it has been shown that such a TFA treatment can lead to a certain amount of depurination of the oligonucleotide [34,38]. The research groups of Gait and Herdewijn both proved that removal of the Boc group from imidazole during standard deprotection procedures with saturated methanolic ammonia after oligonucleotide synthesis is possible [35,39], therefore in our second attempt, using urocanic acid (1), the imidazole moiety was Boc-protected using di-tert-butyldicarbonate as shown in Scheme 1. N Im -Boc-protected urocanic acid 2 was further coupled with the dimethoxytrityl protected 2'-amino-2'-deoxyuridine 4 in the presence of N- (3-dimethylaminopropyl)-N'-ethylcarbodiimide (EDC) and N-hydroxysuccinimide (NHS) to give 5 in 68% yield.…”
Section: Resultsmentioning
confidence: 97%
“…However, the DNP protection did not survive conditions used during purification of the final DMTr-protected nucleoside. Because it has further been proven that the DNP group gives yellow contaminated products after deprotection, we decided to change the protecting group into a tert-butoxycarbonyl (Boc) one [34], which is compatible with the reagents used during nucleoside-and oligonucleotide synthesis [35][36][37]. In principle, removal of the Boc group on a solid support can be accomplished with a 10% TFA solution after automated synthesis [37].…”
Section: Resultsmentioning
confidence: 99%